Development of a multivariable model to predict vulnerability in older American patients hospitalised with cardiovascular disease. Issue 8 (27th August 2015) - Bell, Susan P; Schnelle, John; Nwosu, Samuel K; Schildcrout, Jonathan; Goggins, Kathryn; Cawthon, Courtney; Mixon, Amanda S; Vasilevskis, Eduard E; Kripalani, Sunil
Abstract : Objectives: To identify vulnerable cardiovascular patients in the hospital using a self-reported function-based screening tool. Participants: Prospective observational cohort study of 445 individuals aged ≥65 years admitted to a university medical centre hospital within the USA with acute coronary syndrome and/or decompensated heart failure. Methods: Participants completed an inperson interview during hospitalisation, which included vulnerable functional status using the Vulnerable Elders Survey (VES-13), sociodemographic, healthcare utilisation practices and clinical patient-specific measures. A multivariable proportional odds logistic regression model examined associations between VES-13 and prior healthcare utilisation, as well as other coincident medical and psychosocial risk factors for poor outcomes in cardiovascular disease. Results: Vulnerability was highly prevalent (54%) and associated with a higher number of clinic visits, emergency room visits and hospitalisations (all p<0.001). A multivariable analysis demonstrating a 1-point increase in VES-13 (vulnerability) was independently associated with being female (OR 1.55, p=0.030), diagnosis of heart failure (OR 3.11, p<0.001), prior hospitalisations (OR 1.30, p<0.001), low social support (OR 1.42, p=0.007) and depression (p<0.001). A lower VES-13 score (lower vulnerability) was associated with increased health literacy (OR 0.70, p=0.002). Conclusions: Vulnerability to functional decline is highly prevalent in hospitalised older cardiovascular patients and was associated with patient risk factors for adverse outcomes and an increased use of healthcare services.